2013
DOI: 10.1371/journal.pone.0062364
|View full text |Cite
|
Sign up to set email alerts
|

The Application of the Ten Group Classification System (TGCS) in Caesarean Delivery Case Mix Adjustment. A Multicenter Prospective Study

Abstract: BackgroundCaesarean delivery (CD) rates are commonly used as an indicator of quality in obstetric care and risk adjustment evaluation is recommended to assess inter-institutional variations. The aim of this study was to evaluate whether the Ten Group classification system (TGCS) can be used in case-mix adjustment.MethodsStandardized data on 15,255 deliveries from 11 different regional centers were prospectively collected. Crude Risk Ratios of CDs were calculated for each center. Two multiple logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
4

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 24 publications
3
17
0
4
Order By: Relevance
“…Moreover, mothers with a high BMI are under-represented. However, prepregnancy BMI in our sample reflects that of mothers coming from our region 7. Therefore, our results may not be generalisable to populations with a different maternal nutritional status.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, mothers with a high BMI are under-represented. However, prepregnancy BMI in our sample reflects that of mothers coming from our region 7. Therefore, our results may not be generalisable to populations with a different maternal nutritional status.…”
Section: Discussionmentioning
confidence: 57%
“…First, by taking an aggregate approach, it adds to patient level studies on the determinants of caesarean deliveries (see, e.g., recent examples of different approaches in Maso et al, 2013a;Maso et al, 2013b;Bragg et al 2010;Dranove and Watanabe, 2010;Ecker and Frigoletto, 2007;Fantini et al, 2006;Baicker et al, 2006;Johanson et al, 2006). Second, proposing an analysis at the regional level, the present work is also related to papers on regional variations in health care and in medical practice (e.g., Skinner, 2012, andChandra et al, 2012 for recent surveys).…”
Section: 3) As Regions Represent Inmentioning
confidence: 99%
“…For instance, obesity, chronic hypertension, gestational diabetes are all clinical conditions used in the medical literature to adjust observed caesarean sections for risk, and to define the quality of obstetric care (see, e.g., recent works by Maso et al, 2013a;Maso et al, 2013b;Fantini et al, 2006;Bragg et al 2010 ). All these factors have deteriorated in recent decades.…”
Section: Why Are Caesarean Sections On the Rise? A Brief Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the objective of our study was not to evaluate the adjusted CD rates of each institution, rather to provide a simple and immediate tool to assess which groups and indications contributed to the institutional CD rates [31]. Moreover, we demonstrated that the TGCS risk adjustment either with or without the inclusion of maternal characteristics and obstetrical risk factors, as predictors, might be considered as a reliable method to properly assess inter-institutional variation of CD rates [32]. …”
Section: Commentmentioning
confidence: 99%